A comparative analysis of the efficacy and safety of therapeutic interventions in phlegmasia cerulea dolens. (June 2021) - Said, Ahmad; Sahlieh, Ali; Sayed, Luay
Objective: Present an institution's experience in management of phlegmasia cerulea dolens (PCD) with a review of the literature. Methods: Beaumont Health's electronic record database was queried between July 2009 and November 2019 for inpatients with PCD. A comprehensive chart review was performed to verify the accuracy of the diagnosis and extract relevant parameters. Medians and proportions are reported. Results: 22 patients met the criteria for PCD. 59% females. Median age 65 years (interquartile range [IQR] 22). Obesity was present in 45% of patients. 18 patients underwent either a single modality (55.5%) or a multimodality therapeutic approach (44.5%). Limb amputation was required in a third of patients who underwent catheter-directed thrombolysis or percutaneous thrombectomy alone. Death was highest after percutaneous thrombectomy alone (66%) followed by pharmacomechanical catheter-directed thrombolysis alone (50%). Conclusion: Percutaneous interventions have become the mainstay in management of PCD as demonstrated in this large retrospective analysis and supported by literature review.